Effectiveness of the Fourth Dose: Clinical-Epidemiological Comparison between Covid-19 Infections in Vaccinated People with and without 4th Dose of Vaccines Bivalent mRNA in the Period from October 2022 to February 2023 - Turabian, Jose Luis (International Research in Medical and Health Sciences, 2023)
Background: The effectiveness of the 4th dose of mRNA covid-19 vaccine is not clearly known.Objective: To compare the cases of covid-19 in vaccinated 4th dose people with bivalent mRNA vaccines from Comirnaty and Spikevax vaccines vs. cases of covid-19 in not vaccinated 4th dose people and assess their relative effectiveness.Methodology: An observational, longitudinal, and prospective case series study of adult patients with covid-19 infections in general medicine from October 1, 2022, to February 28, 2023Results: Five cases of covid-19 infections in vaccinated people with 4th dose (3 from COMIRNATY BIVALENTE and 2 from SPIKEVAX BIVALENTE) and 31 cases of covid-19 infections in vaccinated people without 4th dose were included. The cases with the 4th dose had a higher mean age (65.6 +- 22.42 vs. 48.41 +- 14.29; t-value= 2.30361), more Endocrine chronic diseases (32% vs. 8%; Fisher exact test= 0.0276) and less Digestive (4% vs. 24%; X2= 3.9082. p= .048052). In both groups General symptoms prevailed followed by ENT. There were no statistically significant differences between those vaccinated and not vaccinated with the 4th dose for the rest of the variables, but the cases with the 4th dose had more chronic diseases (80% vs. 45%), more Circulatory system chronic diseases (32% vs. 14 %) and diseases of the blood (9% vs 0%), and less Respiratory system chronic diseases (0% vs. 8%), and Genitourinary (4% vs. 16%). 4th dose vaccine covid-19 effectiveness (calculated as 1 - [Covid-19 cases with 4th vaccine dose / Covid-19 cases without 4th vaccine dose] × 100) was 84%.Conclusion: In the general practice setting in Toledo, Spain, from October 1, 2022, to February 28, 2023, the effectiveness of the 4th dose of mRNA bivalent vaccine against covid-19 was high.